Temporary Migration Decisions and Effects on Household Income and Diets in Rural Bangladesh - Md. Sohel Rana; Amy Faye; Matin Qaim (Agricultural Economics, 2025)
Temporary migration is a widely observed phenomenon among poor rural households, yet often overlooked by policy-makers and not captured well in standard household surveys. Although temporary migration is often related to agricultural seasonality, household preferences for temporary over longer-term migration, and the differential effects of these two types of migration on livelihoods, are not yet well understood. Here, we use survey data collected in northern Bangladesh to analyze determinants of households' choice between temporary and longer-term migration, and effects on various livelihood indicators. Issues of selection bias and endogeneity are addressed with instrumental variables. We show that temporary migration is more common than longer-term migration in poor agrarian societies, partly determined by socioeconomic and family demographic constraints. Although longer-term migration has larger positive effects on household income, temporary migration has larger positive effects on food consumption and dietary quality during lean periods. Our results suggest that temporary migration is an important strategy for poor rural households to cope with risks and therefore deserves more explicit attention in research and policy.
Keywords: 330; agricultural seasonality; Bangladesh; food security; nutrition; temporary migration